Utilization of Key Images toward Enhancing Text Informativeness - Sargsyan, Mariana (Armenian Folia Anglistika, 2013)
The article aims to further develop our all-around study of symbol-images trying to combine the results of the examination of ideological and aesthetic aspects of key images that function as symbols with the informative function of the image. In this regard, the argument that one of the key goals of a text, including a literary text, is to convey information, is beyond any doubt. This is accomplished through linguostylistic devices and intrinsic meanings of units comprising various levels of the text which, due to the tactics and intention of the author, contain the whole valuable information of the perception and interpretation of the text. The informative value of key images is not stable in itself depending on the quality and volume of the valuable information, the readers’ ability to interpret, as well as the availability of the background knowledge. The disclosure of the valuable information contained in the key images makes it possible to perceive the tactical intent of the author, to penetrate into the content proper of the work and share the emotions of the author. Due to the origin and depth of the information contained, key images can help the reader establish a dialogue with secondary texts, which comes to indicate that it is possible to move from one text to others through symbol-images thereby creating intertextual bonds.